2010
DOI: 10.1680/macr.9.00063
|View full text |Cite
|
Sign up to set email alerts
|

Studying the production process and mechanical properties of reactive powder concrete: a Hong Kong study

Abstract: Reactive powder concrete is a relatively new cementitious material. Its main features include a high percentage ingredient of Portland cement, very low water-to-binder (cement + silica fume) ratio, a high dosage of superplasticiser and the presence of very fine crushed quartz and silica fume. Coarse aggregate in normal aggregate concrete is completely replaced by fine quartz sand with particle sizes ranging from 150 to 600 ìm. Reactive powder concrete is characterised by ultra-high performance in mechanical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…Several researchers accomplishes the observations on RPC material in past, conducts the attractive survey on definite materials. Analysts have considered on picking fixings, decision of relieving administration, molecule pressing of blend [3] built up a ultra-high quality pliable cement composed RPC material with essential standards of improving the constituent based on wiping out of the unrefined total, upgrading the micro-structure by pre-set affability treatment, likewise, flexibility and rigidity of cement is expanded by fusing little, large ductile, straight microfibers [4]. Two kinds of cements are produced and assigned as RPC material 200 and RPC material 800.…”
Section: Literature Surveymentioning
confidence: 99%
“…Several researchers accomplishes the observations on RPC material in past, conducts the attractive survey on definite materials. Analysts have considered on picking fixings, decision of relieving administration, molecule pressing of blend [3] built up a ultra-high quality pliable cement composed RPC material with essential standards of improving the constituent based on wiping out of the unrefined total, upgrading the micro-structure by pre-set affability treatment, likewise, flexibility and rigidity of cement is expanded by fusing little, large ductile, straight microfibers [4]. Two kinds of cements are produced and assigned as RPC material 200 and RPC material 800.…”
Section: Literature Surveymentioning
confidence: 99%
“…From the definition of RPC, a fine aggregate for concrete is taken in two or three fractions [9][10][11]14]. For example, a coarse fraction of an average of 0.3 mm in an amount of 80% and a small fraction of 0.12 mm -20%, which provides a significant reduction in its intergranular voids.…”
Section: Introductionmentioning
confidence: 99%
“…The first UHPC road bridge was designed and constructed at Bourg-les-Valence in France in 2001 [2]. The preparation and performance of UHPC have been investigated in other literatures [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the experimental results, it is found that reactive powder concrete with a water-to-binder ratio of 0.2, superplasticizer dosage of 2.5%, 150-600 micron quartz sand cured at 27 ᵒ C in water condition provides the best results in terms of mechanical and composite properties as well as for practical and economical reasons, although heat treatment of the reactive powder concrete can result in a significant increase in compressive strength. K.M.Ng et al (2010) [4] attempt to produce reactive powder concrete using local materials under laboratory conditions. Concrete designed from reactive powder concrete and high-performance concrete is experimentally conducted and compared.…”
Section: Introductionmentioning
confidence: 99%